Endoscopic Bilateral Optic Nerve Decompression for Treatment of Idiopathic Intracranial Hypertension - Goksu, Ethem; Bozkurt, Baran; Ilhan, Deniz; Ozak, Ahmet; Cirak, Musa; Yagmurlu, Kaan (MDPI, 2021)
Objective: To evaluate the results of bilateral endoscopic optic nerve decompression (EOND) with the opening nerve sheath (ONS) technique in patients with idiopathic intracranial hypertension (IIH). Methods: Between the years of 2017 and 2019, we retrospectively evaluated nine IIH patients with progressive visual impairment despite medical treatment and who were treated with the EOND and ONS techniques. We also demonstrated our surgical technique recipe on postmortem human heads in a stepwise manner. Results: There were 9 patients (7 females and 2 males) between the ages of 21 and 72 included in this study, and the mean age was 40.8. All patients had an impairment in visual acuity and/or their visual field, with signs of papilledema and/or optic atrophy. The patients were followed up with for 9-48 months. Improvements in visual acuity were observed in 7 out of 9 patients (78\%). Visual field defects improved in 5 out of 8 patients (62.5\%). Papilledema was resolved in all patients (100\%). Headaches improved in all symptomatic patients (100\%). No intraoperative or postoperative complications were observed. Conclusions: EOND is a safe and effective surgical procedure in selected patients with IIH. Bilateral wide bony decompression and nerve fenestration can also be an additional benefit for headache relief. Further clinical series and long-term follow-up are needed for more precise results.
Keywords: idiopathic intracranial hypertension; endoscopic optic nerve decompression; nerve sheath fenestration